Facile Synthesis of Magnetic Activated Carbon Composite for Arsenic Adsorption - Karki, Bivek; Pandey, Pragya; Rajbhandari, Rinita; Joshi, Sahira; Koirala, Agni Raj; Sharma, Ram Kumar; Pant, Hem Raj (Journal of the Institute of Engineering, 2019)
Porous activated carbon (AC) and magnetic iron oxide nanoparticles (NPs) are widely used for the removal of arsenic from water body. Fabrication of composite material of iron oxide NPs on the surface of porous AC can further enhance this activity for commercial application. In this research, a magnetic AC composite for arsenic adsorption was prepared by facile hydrothermal treatment of aqueous solution containing activated carbon obtained from lapsi seed stone, iron(II) chloride, polyvinylpyrrolidone (PVP) and ethanol. Several analytical techniques such as scanning electron microscopy (SEM), energy dispersive x-ray (EDX), X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the formation of magnetite (Fe3O4) nanoparticles on the surface of porous AC. The prepared materials were accessed for their arsenic adsorption capacity using arsenic (III) trioxide solution and found that composite Fe2O3/AC can remove the arsenic from water far more effectively than activated carbon alone. For 0.5 g/ltr loading of composite sample with contract time of 5 hours, the arsenic content was significantly reduced, which shows that as-fabricated composite can be used potentially for water treatment.